Pengaruh Daun Bayam Hijau (Amaranthus Hybidrus L.) sebagai Hair Tonic Rambut Rontok - Azzahra Putri Zayes; Merita Yanita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study is motivated by conditions affecting the scalp and hair, one of which is hair loss. To prevent this issue, hair care is conducted using hair tonic as it is more effective in nourishing hair. The objective of this research is to analyze the effect of hair loss treatment through the use of hair tonic made from Green Spinach Leaves, applied once a week and twice a week over a one-month period. This research employs a quasi-experimental method with a Nonequivalent Control Group Design. The population consists of students from the Beauty and Aesthetics Department, class of 2020. Sampling is conducted using Purposive Sampling technique. Data collection methods include observation, documentation, and assessment sheets. Data analysis techniques utilized are Normality Test, Homogeneity Test, and Hypothesis Test. The results of the Normality Test indicate that the data is normally distributed, with significance scores of 0.120 for the control group (X₀), 0.200 for Experimental Group 1 (X₁), and 0.200 for Experimental Group 2 (X₂). The Homogeneity Test yields a significance value of 0.327, which is greater than 0.05, indicating that the data is homogeneous. Based on the ANOVA test, the significance score is 0.001, which is less than 0.05, leading to the acceptance of the alternative hypothesis (Ha). This indicates significant differences among the three groups, which is further analyzed using Duncan's test. The results conclude that the control group (X₀) with an average of 96.42 significantly differs from Experimental Group 1 (X₁) with an average of 68.33, while X₁ does not significantly differ from Experimental Group 2 (X₂) with an average of 62.33. Thus, it is concluded that there is a significant difference between X₀ and X₁, while X₁ and X₂ do not differ significantly.